PRESIDENTIAL THRESHOLD IN SUMULTANEOUS ELECTION AFTER THE ENACTMENT OF THE LAW NUMBER 7 OF 2017 ON GENERAL - Istyawati, Astri (JOURNAL EQUITABLE, 2018)
The enactment of the Law Number 7 of 2017 on General Election has created some controversies. One of those controversies is about Presidential Threshold, whether it is still needed or not as the upcoming Presidential Election and Legislative Election in General Election 2019 will be held simultaneously. This research is normative legal research with statute and comparative approaches. The result of this study shows that the Presidential Threshold in the upcoming simultaneous election in 2019 still has some problems. Firstly, the Presidential Threshold is not relevant if it is implemented in general election 2019. The second problem is the dilemma in choosing the alternative election for using Presidential Threshold. This research proposes some recommendations. First, the DPR should revise the Article 222 on the Presidential Threshold of the Law Number 7 of 2017 on General Election, regarding to the upcoming election in 2019 that will be hold simultaneous so there should be no Presidential Threshold. Second, the DPR should choose a better model of the Presidential Election whether the election is the separate election as implemented or the Presidential Threshold or simultaneous election.